IMPROVING ENGLISH COMMUNICATIVE COMPETENCE FOR VOCATIONAL HIGH SCHOOL USING SCAFFOLDING TEHNIQUE - Ratini Setyowati; Beta Setyowati; Evi Murti Wardhani (Universitas Duta Bangsa Surakarta, 2020)
Indonesia must prepare the high-skill categories needs for every aspects. One of the aspects is theability to compete in this era, the ability to communicate with other. Indonesian needs Englishcommunicative skill to face the Industrial Revolution 4.0. The aims of the study are: to understandVocational High School students’ English competence and to understand the effect of ScaffoldingTehnique on Improving English Communicative competence for Vocational High School. This researchused descriptive qualitative method. The study used a pre-test, post-test to know the result of the study:the researcher tested the participants orally as the pre-test and post-test of study. In this research, thepopulation of the research is the first grade of Citra Medika Vocational High School. There were 2classes and there were 54 students and all the students are the population of the research. The resultsof independent sample t-test showed that there was a significant difference between the performance ofintervening and control groups (t = 4.60, p< .05) on posttest in such a way that the intervening groupoutperformed in posttest